Transcriptomic Changes Resulting From STK32B Overexpression Identify Pathways Potentially Relevant to Essential Tremor - Liao, Calwing; Sarayloo, Faezeh; Vuokila, Veikko; Rochefort, Daniel; Akçimen, Fulya; Diamond, Simone; Houle, Gabrielle; Laporte, Alexandre D.; Spiegelman, Dan; He, Qin; Catoire, Hélène; Dion, Patrick A.; et al. (Frontiers in Genetics, 2020)
Objective: Essential tremor (ET) is a common movement disorder that has a high heritability. A number of genetic studies have associated different genes and loci with ET, but few have investigated the biology of any of these genes. STK32B was significantly associated with ET in a large GWAS study and was found to be overexpressed in ET cerebellar tissue. The objective of this study is to determine the effects of overexpressed STK32B in cerebellar DAOY cells. Methods: Here, we overexpressed STK32B RNA in human cerebellar DAOY cells and used an RNA-Seq approach to identify differentially expressed genes by comparing the transcriptome profile of these cells to the one of control DAOY cells. Results: Pathway and gene ontology enrichment identified axon guidance, olfactory signalling and calcium-voltage channels as significant. Additionally, we show that overexpressing STK32B affects transcript levels of previously implicated ET genes such as FUS. Conclusions: Our results investigate the effects of overexpressed STK32B and suggest that it may be involved in relevant ET pathways and genes.